ANALYSIS OF CURRENT ISSUES AND DEVELOPMENT PROSPECTS OF PHYSICAL CULTURE AND SPORTS FOR ADULT POPULATION IN UKRAINE AND EUROPEAN COUNTRIES (Physical Culture and Sport: Scientific Perspective, 2023)
The article presents the results of an analysis of current problems and prospects for the development of physical culture and sports for adult population in Ukraine and European countries. The article provides research results demonstrating the decrease in the level of physical activity among adults and its negative impact on health. The problematic aspects of ensuring access to sports infrastructure and promoting physical activity for adults in various European countries, including Ukraine, are also discussed. The article highlights the key issues of this analysis, namely: the health of the adult population, social benefits, accessibility issues, sports infrastructure development, expansion of the range of sports activities, and prospects for the development of physical culture and sports. According to the European Centre for Disease Prevention and Control (ECDC) for 2019, Ukraine has a high proportion of deaths from cardiovascular diseases (46.6% of all deaths) and cancer (18.4% of all deaths). The authors of the article emphasize the need for national and international policies on sports and physical culture for adults, improving the effectiveness of programs and events aimed at popularizing physical activity and maintaining the health of the population. There are many initiatives in the European Union that support physical activity and sports for adult population. For example, the "European Week of Sport" initiative promotes awareness of the importance of physical activity and sports in daily life and stimulates people to live a more active lifestyle. There are approximately 300,000 sports clubs in the European Union. There are many specialized centers in Europe for training and preparing athletes, such as the National Centre for Sports Training in Clermont-Ferrand, INSEP in France, the National Centre for Sports Training in Bispingen, Germany, and The National Sports Centre at Bisham Abbey in Cambridge, UK. Overall, the article contains important information for those dealing with health and physical activity issues among adult population.
Keywords: aspects; physical culture and sports for adult population